Pemodelan dan Analisis Perilaku Balok Beton Bertulang yang Berbeda Diameter Akibat Variasi Tata Letak Tulangannya - Suku, Yohanes Laka (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Analysis of the effect of the layout of reinforcement in reinforced concrete beams with different diameters to understand behavior and layout position of reinforcement produces the maximum of load capacity and ductility. Modeling and analysis using ANSYS program, the experimental test beam type OA1 and A1 from the University of Toronto (Vichio & Shim, 2004) was used as a benchmark and models which varies in layout of reinforcement. The number of models analyzed is a total of fourteen models consisting of seven models without stirrups and seven with stirrups. Beam behavior observed in the form of load capacity, deflection, ductility, stiffness and crack patterns. Results showed that: the layout of reinforcement affects the behavior of reinforced concrete beam; on the same width of reinforcedment, one layer reinforcement has greater load capacity and rigidity but smaller ductility than two layers; the layout of reinforcement in general does not affect the pattern of cracks; the collapse of the beam without stirrups is caused by the diagonal tension and  the beam with stirrups by shear and rupture due to the press; the layout of reinforcement produces the largest load capacity and ductility of the largest is model OA1 and OA1,4 on the beams without stirrups and models A1 and A1,5 on beam with stirrups.